Estrogen Receptor and Vascular Aging - Davezac, Morgane; Buscato, Melissa; Zahreddine, Rana; Lacolley, Patrick; Henrion, Daniel; Lenfant, Francoise; Arnal, Jean-Francois; Fontaine, Coralie (Frontiers in Aging, 2021)
Cardiovascular diseases remain an age-related pathology in both men and women. These pathologies are 3-fold more frequent in men than in women before menopause, although this difference progressively decreases after menopause. The vasculoprotective role of estrogens are well established before menopause, but the consequences of their abrupt decline on the cardiovascular risk at menopause remain debated. In this review, we will attempt to summarize the main clinical and experimental studies reporting the protective effects of estrogens against cardiovascular diseases, with a particular focus on atherosclerosis, and the impact of aging and estrogen deprivation on their endothelial actions. The arterial actions of estrogens, but also part of that of androgens through their aromatization into estrogens, are mediated by the estrogen receptor (ER) and ER. ERs belong to the nuclear receptor family and act by transcriptional regulation in the nucleus, but also exert non-genomic/extranuclear actions. Beside the decline of estrogens at menopause, abnormalities in the expression and/or function of ERs in the tissues, and particularly in arteries, could contribute to the failure of classic estrogens to protect arteries during aging. Finally, we will discuss how recent insights in the mechanisms of action of ER could contribute to optimize the hormonal treatment of the menopause.